Decoupling and robust decoupling for multivariable generalized predictive control design - Qin, Xiao Fan (2009)
Most practical control problems are dominated by process uncertainties and cross-couplings. Although a rich theory has been developed for the robust control of linear SISO (single input-single output) systems, very little is known about the robust de-coupling control of MIMO (multi input-multi output) systems with nonlinearities and uncertainties. It is the goal of this thesis to study such a theory.